PERBANDINGAN DIKSI DAN METAFORA DALAM KUMPULAN PUISI “PERCINTAAN” DAN “365 HARI” - Muhammad Amirul Halim; Gatot Sarmidi (JURNAL ILMIAH BAHASA DAN SASTRA, 2023)
A collection of Love Poems will be published by Penari Pena Publisher in 2022 as well as a book Collection of Poetry 365 Days. This poem is the first work produced by students, so it becomes the interest of researchers to further examine the diction and metaphors in the poem. Based on the problems found, the researcher wants to compare the diction and metaphors between the Love Poetry Collection and 365 Days. This study uses a qualitative approach and is examined based on descriptive methods. Research Location at PGRI University Kanjuruhan Malang. The data of this study are in the form of the entire text, metaphorical sub-text, words/diction, and a collection of words in the Collection of Love Poems and 365 Days. While the data source for this research is the text of Collection of Love Poems and 365 Days published by Penari Pena Publisher (2022). Data Collection and Information Analysis was carried out based on observation and interview techniques. Data analysis was carried out based on interactional data analysis techniques and hermeneutical interpretation. Based on the results of the study it was concluded that the works in the collection of poems contain many hidden messages and different sense values. In addition to connotative sentences, denotative sentences are also found, namely sentences with true meaning. Meanwhile, there are also metaphorical figures of speech, although this figure of speech does not dominate.